Experimental Studies on the Critical Reynolds Number in the Flow of a Microencapsulated Phase Change Material Slurry - Krzysztof Dutkowski; Marcin Kruzel (Energies)
The disadvantage of phase change materials (PCMs) that store thermal energy is their low thermal conductivity. The macro-, micro-, and nanoencapsulation of PCMs are some of the ways to eliminate this drawback. Liquids with micro- and nanometer-sized capsules containing PCMs have become innovative working fluids for heat transfer—a slurry of encapsulated PCMs. This paper shows the results of in-depth studies on the nature of fluid movement (slurry of microencapsulated PCMs) in pipe channels. The slurry flowed inside a tube with a diameter of 4 mm in the range of Re = 350–11,000. The PCM microcapsule (mPCM) concentration ranged from 4.30% to 17.2%. A pressure loss measurement was carried out on a section of 400 mm. The temperature of the flowing slurry was selected so that the PCMs in the microcapsules were in a liquid state and were solid during subsequent measurement series after undergoing a phase transformation. It was found that the boundary of the transition from laminar to turbulent flow is influenced by both the mPCM concentration in the slurry and the state of matter of the PCMs in the microcapsules. The influence of the slurry concentration and the state of matter of the PCMs in the microcapsules on changes such as fluid movement is presented (in terms of the critical Reynolds number).